2018
DOI: 10.3389/fnins.2018.00607
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gonadotropin-Releasing Hormone (GnRH) Genes From Cartilaginous Fish: Evolutionary Perspectives

Abstract: The neuropeptide gonadotropin-releasing hormone (GnRH) plays an important role in the control of reproductive functions. Vertebrates possess multiple GnRH forms that are classified into three main groups, namely GnRH1, GnRH2, and GnRH3. In order to gain more insights into the GnRH gene family in vertebrates, we sought to identify which paralogs of this family are present in cartilaginous fish. For this purpose, we searched the genomes and/or transcriptomes of three representative species of this group, the sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…The main aim of the present study was to determine the repertoire of the SST gene family in cartilaginous fish. For this purpose, the genome and/or transcriptome databases from three representative chondrichthyan species were examined, namely the small-spotted catshark S. canicula (unpublished, see Gaillard et al 2018 for more details), the whale shark, R. typus (Read et al 2017) and the elephant shark C. milii (Venkatesh et al 2014). In S. canicula, two new SST genes, named SSTd and STTe were found, in addition to the three SST genes, SSTa, SSTb and SSTc, previoulsly identified .…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of the present study was to determine the repertoire of the SST gene family in cartilaginous fish. For this purpose, the genome and/or transcriptome databases from three representative chondrichthyan species were examined, namely the small-spotted catshark S. canicula (unpublished, see Gaillard et al 2018 for more details), the whale shark, R. typus (Read et al 2017) and the elephant shark C. milii (Venkatesh et al 2014). In S. canicula, two new SST genes, named SSTd and STTe were found, in addition to the three SST genes, SSTa, SSTb and SSTc, previoulsly identified .…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely recognized that while less evolved teleost species such as salmonids and cyprinids possess two Gnrh isoforms, the brain of most teleost species, including Perciformes, Pleuronectiformes and many other fish orders, exhibit three distinct forms of Gnrh (Kah et al, 2007;Zohar et al, 2010;Choi, 2018). Interestingly, three isoforms of Gnrh were found in the superclass Agnatha and also recently across the non-teleost, cartilaginous fish (Gaillard et al, 2018).…”
Section: The Discovery Of Gnrh Isoformsmentioning
confidence: 99%
“…For example, the GnRH1 genes of both medaka and human lie adjacent to a gene for a potassium channel tetramerization domain containing 9 (KCTD9) and GnRH2 genes are adjacent to a gene for protein tyrosine phosphatase A (PTPRA) (Okubo et al 2002). The syntenies in the GnRH gene loci are also preserved in several other vertebrate species, including chimpanzees, mice, chickens, the pufferfish Tetraodon nigroviridis and Takifugu rubripes, zebrafish, lamprey and sharks (Morgan and Millar, 2004;Kuo et al, 2005;Ikemoto and Park, 2006;Tostivint, 2011;Decatur et al 2013;Gaillard et al, 2018). It is now suggested that GnRH1, GnRH2 and GnRH3 genes represent three paralogous genes resulting from the two rounds (2R) of tetraploidization that took place early in vertebrate evolution, followed by two separate deletion events (Figure 2) (Kim et al 2011;Tostivint, 2011;Roch et al, 2014).…”
Section: Evolution Of Gnrh Isoformsmentioning
confidence: 99%
“…GnRH is a decapeptide produced in the hypothalamus with a regulatory function in the reproductive system (32)(33)(34). Different analogs of GnRH with different half-life exist (22).…”
Section: Discussionmentioning
confidence: 99%